Retrospective Analysis of Clinical Genetic Testing in Pediatric Primary Dilated Cardiomyopathy: Testing Outcomes and the Effects of Variant Reclassification. Issue 11 (2nd June 2020) - Quiat, Daniel; Witkowski, Leora; Zouk, Hana; Daly, Kevin P.; Roberts, Amy E.
Abstract : Background: Genetic testing in pediatric primary dilated cardiomyopathy (DCM) patients has identified numerous disease‐causing variants, but few studies have evaluated genetic testing outcomes in this population in the context of patient and familial clinical data or assessed the clinical implications of temporal changes in genetic testing results. Methods and Results: We performed a retrospective analysis of all patients with primary DCM who presented to our institution between 2008 and 2018. Variants identified by genetic testing were reevaluated for pathogenicity on the basis of current guidelines for variant classification. A total of 73 patients with primary DCM presented to our institution and 63 (86%) were probands that underwent cardiomyopathy‐specific gene testing. A disease‐causing variant was identified in 19 of 63 (30%) of cases, with at least 9/19 (47%) variants occurring de novo. Positive family history was not associated with identification of a causal variant. Reclassification of variants resulted in the downgrading of a large proportion of variants of uncertain significance and did not identify any new disease‐causing variants. Conclusions: Clinical genetic testing identifies a causal variant in one third of pediatric patients with primary DCM. Variant reevaluation significantly decreased the number of variants of uncertain significance, but a large burden of variants of uncertain significance remain. These results highlight the need for periodic reanalysis of genetic testing results, additional investigation of genotype‐phenotype correlations in DCM through large, multicenter genetic studies, and development of improved tools for functional characterization of variants of uncertain significance.